2021
DOI: 10.1007/s00787-020-01714-1
|View full text |Cite
|
Sign up to set email alerts
|

Hair cortisol-a stress marker in children and adolescents with chronic tic disorders? A large European cross-sectional study

Abstract: Background There is clear evidence that tic disorders (TDs) are associated with psychosocial stress as well as emotional and behavioral problems. Studies have shown that individuals with TDs have higher acute physiological stress responses to external, single stressors (as reflected by saliva cortisol). The aim of the present study was to examine a physiological marker of longer-term stress (as reflected by hair cortisol concentration) in children and adolescents with TDs and unaffected siblings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In addition, high quality studies with hair hormone measurement are currently evolving with associations between hair hormones and mental disorders (exemplarily: [15,54,76,94,95] or considering methodological issues [9,31,47]. Regarding the methodological challenges, diurnal steroid hormone levels (e.g., measured via saliva or urine samples) and longer-term steroid hormone levels (measured via hair samples) should be investigated congruently in longitudinal studies to compare the characteristics of the sampling methods [18]. An alternative explanation for the weak associations in the present study relates to the genetic background, particularly the androgen receptor CAG repeat.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In addition, high quality studies with hair hormone measurement are currently evolving with associations between hair hormones and mental disorders (exemplarily: [15,54,76,94,95] or considering methodological issues [9,31,47]. Regarding the methodological challenges, diurnal steroid hormone levels (e.g., measured via saliva or urine samples) and longer-term steroid hormone levels (measured via hair samples) should be investigated congruently in longitudinal studies to compare the characteristics of the sampling methods [18]. An alternative explanation for the weak associations in the present study relates to the genetic background, particularly the androgen receptor CAG repeat.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…A prospective longitudinal study described that a multiplicative interaction between GABHS infections and psychosocial stress can enhance tic and OC symptom severity (Lin et al, 2010). Psychosocial stress, a strong predictor of greater tic severity, may also influence immune responses to infection via activation of the hypothalamic-pituitaryadrenal axis (Martino et al, 2020), although this mechanism is yet not fully understood (Buse et al, 2021). Finally, behavioural patterns, which may be accentuated in young people with greater tic severity and/or a higher comorbid neuropsychiatric burden, could increase the risk of exposure to infectious pathogens (Martino et al, 2020) and, thus, also indirectly contribute the association observed in thus study.…”
Section: Discussionmentioning
confidence: 89%
“…The study authors concluded that GAS exposure was less likely to be a risk factor for tic exacerbations; therefore, the evaluation and treatment of GAS infections are not warranted in the context of worsening of tics. The authors also attempted to identify biomarkers of tics, examining hair cortisol concentration as a physiological marker of long-term stress in patients with tics, and found no association between hair cortisol concentration and tic severity 61 .…”
Section: Etiologymentioning
confidence: 99%